Novel Coagulation Analyzers in Development: A Glimpse toward the Future of Microfluidics - Emani, Sitaram M. (Seminars in Thrombosis and Hemostasis, 2019)
Coagulation diagnostic testing in pediatric patients currently requires large volume blood sampling and is performed on analyzers that are not well-suited for multiplexed assays on a given sample. For patients who require serial testing at regular intervals, repetitive phlebotomy leads to iatrogenic anemia and need for blood transfusions. Over the past decade, novel microfluidic platforms have been developed that allow for complex multiplexed assays to be performed on small sample volumes, near patient, with high fidelity. In the next few years, these devices will be introduced into clinical trials, and offer the promise of reliable, rapid, multiplexed coagulation assays for pediatric patients who require coagulation diagnostic testing.
Keywords: coagulation analyzers; microfluidics; development